2014
DOI: 10.1038/tp.2013.112
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism of the nucleus accumbens and ventral pallidum 5-HT1B receptors underlying the antidepressant action of ketamine: a PET study with macaques

Abstract: Ketamine is a unique anesthetic reagent known to produce various psychotic symptoms. Ketamine has recently been reported to elicit a long-lasting antidepressant effect in patients with major depression. Although recent studies provide insight into the molecular mechanisms of the effects of ketamine, the antidepressant mechanism has not been fully elucidated. To understand the involvement of the brain serotonergic system in the actions of ketamine, we performed a positron emission tomography (PET) study on non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 49 publications
2
55
0
Order By: Relevance
“…isoflurane, have been shown to decrease cortical extracellular serotonin concentration (Mukaida et al 2007) and to increase [ 3 H]escitalopram binding in rats (Elfving et al 2003). Moreover, in a paradigm more similar to the current study, sub-anaesthetic doses of ketamine have recently been shown to decrease [ 11 C]DASB binding by up to 30 % in NHPs (Yamamoto et al 2013;Yamanaka et al 2014). In the current and previous SERT occupancy studies (Batis et al 2012;Cosgrove et al 2010), ketamine was used to induce anaesthesia and baseline PET measurements may therefore be more affected by ketamine than the post-SSRI measurements.…”
Section: Discussionsupporting
confidence: 49%
“…isoflurane, have been shown to decrease cortical extracellular serotonin concentration (Mukaida et al 2007) and to increase [ 3 H]escitalopram binding in rats (Elfving et al 2003). Moreover, in a paradigm more similar to the current study, sub-anaesthetic doses of ketamine have recently been shown to decrease [ 11 C]DASB binding by up to 30 % in NHPs (Yamamoto et al 2013;Yamanaka et al 2014). In the current and previous SERT occupancy studies (Batis et al 2012;Cosgrove et al 2010), ketamine was used to induce anaesthesia and baseline PET measurements may therefore be more affected by ketamine than the post-SSRI measurements.…”
Section: Discussionsupporting
confidence: 49%
“…Given the various underlying serotonergic mechanisms, it is interesting that a lack of 5-HT 1B autoreceptors was sufficient to generate antidepressant and anxiolytic responses. Taken together with studies showing dysregulation of 5-HT 1B Rs in mood disorders in humans (Murrough et al, 2011a,b) and the potential involvement of 5-HT 1B Rs in antidepressant responses (Tiger et al, 2014;Yamanaka et al, 2014), our results suggest the potential benefit of strategies aimed at targeting 5-HT 1B autoreceptor signaling for the treatment of anxiety and depression. …”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, ketamine does not produce antidepressant effects in 5-HT deprived animals [128], suggesting that 5-HT tone is required for ketamine's antidepressant activity. Additional targets of ketamine, such as sigma receptors [129], monoamine transporters [130], and 5-HT 1B receptors [131], as well as pharmacological activities of ketamine's metabolites, might collectively contribute to its antidepressant effect. Thus, additional research is needed to elucidate ketamine's mechanism of action.…”
Section: Ketamine and Other Nmda Receptor Modulatorsmentioning
confidence: 99%